2006
DOI: 10.1073/pnas.0603369103
|View full text |Cite
|
Sign up to set email alerts
|

A burst of auxilin recruitment determines the onset of clathrin-coated vesicle uncoating

Abstract: Clathrin-coated pits assemble on a membrane and pinch off as coated vesicles. The released vesicles then rapidly lose their clathrin coats in a process mediated by the ATPase Hsc70, recruited by auxilin, a J-domain-containing cofactor. How is the uncoating process regulated? We find that during coat assembly small and variable amounts of auxilin are recruited transiently but that a much larger burst of association occurs after the peak of dynamin signal, during the transition between membrane constriction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
191
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(222 citation statements)
references
References 35 publications
28
191
2
1
Order By: Relevance
“…It was shown previously that the kinase GAK, which is necessary for CCV uncoating, was recruited shortly after the large GTPase dynamin to sites of CME [15,16]. Here, we found that GAK recruitment commenced at scission and peaked on average ,8 s thereafter, as predicted.…”
Section: The Invariant Recruitment Of Gaksupporting
confidence: 66%
See 2 more Smart Citations
“…It was shown previously that the kinase GAK, which is necessary for CCV uncoating, was recruited shortly after the large GTPase dynamin to sites of CME [15,16]. Here, we found that GAK recruitment commenced at scission and peaked on average ,8 s thereafter, as predicted.…”
Section: The Invariant Recruitment Of Gaksupporting
confidence: 66%
“…The kinase GAK is an established marker for CCV uncoating [15,16], and the GAK recruitment signature was the same for terminal and nonterminal scission events, for scission events at spot-like CCSs that formed de novo, and for scission events at different size and lifetime classes of CCSs.…”
Section: The Properties Of Endocytically Active Ccssmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequentially, this would guarantee selective retention of PI(4,5)P 2 at the plasma membrane and promote uncoating of vesicles immediately after fission (5). The SJ1-mediated change in phosphoinositide composition of the newly formed endocytic vesicle may favor uncoating by decreasing the affinity of clathrin adaptors with the membrane while simultaneously promoting the recruitment of auxilin, a cofactor for the ''uncoating ATPase'' HSC70 (39,40). The importance of SJ1 in clathrin uncoating is strongly supported by the accumulation of clathrin-coated vesicles in nerve terminals of SJ1 knockout mice (3,28).…”
Section: Discussionmentioning
confidence: 83%
“…Le détachement des vésicules de cla thrine de la membrane plasmique requiert l'action de la dynamine, une mécano-enzyme qui induit la fission de la base (« au cou ») de la vésicule [8]. Enfin, le désassemblage du manteau de clathrine de la vésicule nouvellement formée est assuré par l'ATPase Hsc70, recrutée par la protéine auxiline (Figure 1) [9][10][11]. La vésicule poursuit alors son chemin vers les endosomes précoces, et les composants de la machinerie du manteau de clathrine sont de nouveau disponibles pour un cycle.…”
unclassified